CHANGING HAEMATOLOGICAL PARAMETERS IN DENGUE VIRAL INFECTIONS - Jameel, Tahir; Mehmood, Khalid; Mujtaba, Ghulam; Choudhry, Nakhshab; Afzal, Naeema; Paul, Rubina Faisal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Dengue Fever is the most common arboviral disease in the world, and presents cyclically in tropical and subtropical regions of the world. The four serotypes of dengue virus, 1, 2, 3, and 4, form an antigenic subgroup of the flaviviruses (Group B arboviruses). Transmission to humans of any of these serotypes initiates a spectrum of host responses, from in apparent to severe and sometimes lethal infections. Complete Blood count (CBC) is an important part of the diagnostic workup of patients. Comparison of various finding in CBC including peripheral smear can help the physician in better management of the patient. Material and Methods: This cross sectional study was carried out on a series of suspected patients of Dengue viral infection reporting in Ittefaq Hospital (Trust). All were investigated for serological markers of acute infection. Results Out of 341 acute cases 166 (48.7%) were confirmed by IgM against Dengue virus. IgG anti-dengue was used on 200 suspected re-infected patients. Seventy-one (39.5%) were positive and 118 (59%) were negative. Among 245 confirmed dengue fever patients 43 (17.6%) were considered having dengue hemorrhagic fever on the basis of lab and clinical findings. Raised haematocrit, Leukopenia with relative Lymphocytosis and presence atypical lymphocytes along with plasmacytoid cells was consistent finding at presentation in both the patterns of disease, i.e., Dengue Haemorrhagic fever (DHF) and Dengue fever (DF). Conclusion: Changes in relative percentage of cells appear with improvement in the symptoms and recovery from the disease. These findings indicate that in the course of the disease, there are major shifts within cellular component of blood. Keywords: Dengue, Complete Blood count, atypical lymphocyte